2015
DOI: 10.1039/c5dt00704f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of halide, separated ion pair, and hydride cyclopentadienyl iron bis(diphenylphosphino)ethane derivatives

Abstract: Treatment of anhydrous FeX2 (X = Cl, Br, I) with one equivalent of bis(diphenylphosphino)ethane (dppe) in refluxing THF afforded analytically pure white (X = Cl), light green (X = Br), and yellow (X = I) [FeX2(dppe)]n (X = Cl, ; Br, ; I, ). Complexes are excellent synthons from which to prepare a range of cyclopentadienyl derivatives. Specifically, treatment of with alkali metal salts of C5H5 (Cp, series ), C5Me5 (Cp*, series ), C5H4SiMe3 (Cp', series ), C5H3(SiMe3)2 (Cp'', series ), and C5H3(Bu(t))2 (Cp(tt), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 77 publications
4
24
0
Order By: Relevance
“…The hydride ligand of the complex in deuteriobenzene after 30 min shows coupling with two phosphorus atoms and appears as a triplet at –14.24 ppm with J P,H = 72.4 Hz. The chemical shift and the magnitude of the coupling constant are similar to the values found for bis(diphenylphosphino)ethane(cyclopentadienyl)iron hydrides [ R CpFeH(dppe)] with cyclopentadienyl derivatives C 5 H 5 (–15.94 ppm, 2 J P,H 72 Hz), C 5 Me 5 (–16.66 ppm, 72 Hz), C 5 H 4 t Bu (–15.31 ppm, 2 J P,H 72 Hz), C 5 H 4 SiMe 3 (–16.54 ppm, 2 J P,H 72 Hz), and C 5 H 3 t Bu 2 ‐1,3 (–15.65 ppm, 2 J P,H 84 Hz) . These observations indicate the formation of the tetraphenyldiphosphine iron hydride complex [ 5 CpFeH(P 2 Ph 4 )] ( 9 ) from 8 in solution.…”
Section: Resultssupporting
confidence: 77%
“…The hydride ligand of the complex in deuteriobenzene after 30 min shows coupling with two phosphorus atoms and appears as a triplet at –14.24 ppm with J P,H = 72.4 Hz. The chemical shift and the magnitude of the coupling constant are similar to the values found for bis(diphenylphosphino)ethane(cyclopentadienyl)iron hydrides [ R CpFeH(dppe)] with cyclopentadienyl derivatives C 5 H 5 (–15.94 ppm, 2 J P,H 72 Hz), C 5 Me 5 (–16.66 ppm, 72 Hz), C 5 H 4 t Bu (–15.31 ppm, 2 J P,H 72 Hz), C 5 H 4 SiMe 3 (–16.54 ppm, 2 J P,H 72 Hz), and C 5 H 3 t Bu 2 ‐1,3 (–15.65 ppm, 2 J P,H 84 Hz) . These observations indicate the formation of the tetraphenyldiphosphine iron hydride complex [ 5 CpFeH(P 2 Ph 4 )] ( 9 ) from 8 in solution.…”
Section: Resultssupporting
confidence: 77%
“…[24] Iron-hydride distances determined by X-ray diffraction are,b yn ature,s horter.Asearch in the CSD (ConQuest 1.19, 2017) [25] database of related Cp iron hydrides revealed Fe-H distances ranging from 1.34 [26,27] to 1.59 . [28,29] Thes tructures determined from the two data sets recorded at 30 Ka nd 100 Kr evealed slightly bent ferrocene backbones (see Table 1). Thetwo cyclopentadienyl rings are tilted against each other as indicated by the interplanar angles of 14.48 8 (at 30 K) and 11.88 8 (at 100 K) between the two cyclopentadienyl rings.This opens the space to accommodate the hydride ligand.…”
Section: Angewandte Chemiementioning
confidence: 95%
“…This phase transition resulted in the lower symmetry space group P3 1 (No.144) with minimal changes in the lattice parameters,m ostly owing to the lower temperature.The observed symmetry reduction affected the twofold rotation axis along the short diagonal of the unit cell, which now had to be accounted for by an additional twin law. [28,29] Thes tructures determined from the two data sets recorded at 30 Ka nd 100 Kr evealed slightly bent ferrocene backbones (see Table 1). To avoid variations in the CÀHbond lengths of the cyclopentadienyl rings,t hese hydrogen atoms were placed in positions of optimized geometry.T he ironbound hydride hydrogen atom H11, however,was left on the position where it was first located from ad ifference Fourier synthesis,and was allowed to ride on Fe1, resulting in d(Fe1-H11) = 1.62 .T he Fe-H distances observed at 100 K (1.49(4) )a nd 30 K( 1.62 )a gree well with the FeÀH bond lengths of non-bridging hydrides as established by neutron diffraction experiments on iron hydride compounds, which range from 1.513 in dihydrido(dihydrogen-H,H')tris(ethyldiphenylphosphine)iron [23] to 1.615 in an FeH 6 4À anion.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…[50] Most recently, Liddle and colleagues have explored the synthetic chemistry associated with the preparation of a wide range of half-sandwich FeCl(dppe)(η 5 -C5R5) compounds (C5R5 = C5H5 (Cp), C5(CH3)5 (Cp*), C5H4SiMe3, C5H3(SiMe3)2, and C5H3( t Bu)2). [51] In this case FeCl(dppe)Cp* was synthesised (73%) by 1:1 reaction of potassium pentamethylcyclopentadienide with [FeCl2(dppe)]n in toluene (-78 °C → r.t., 18h), though only generalised reaction conditions were given for the series of half sandwich complexes reported. The reaction temperature was noted as being important for achieving the reported yields, with formation of ferrocenes and free 1,2-bis(diphenylphosphino)ethane from ligand scrambling processes being problematic in reactions conducted at room temperature, but being largely eliminated in reactions carried out initially at −78 °C.…”
Section: Fecl(dppe)cp*mentioning
confidence: 99%
“…A more convenient laboratory preparation of FeCl(dppe)Cp* would avoid the use of ultrasonic irradiation, and the isolation and manipulation of air sensitive lithium [52] or pyrophoric potassium [53] pentamethylcyclopentadienides, whilst taking advantage of the ready availability of [FeCl2(dppe)]n. Although [FeCl2(dppe)2]n is commonly prepared from reaction of anhydrous FeCl2 with 1,2-bis(diphenylphosphino)ethane [41,51] it has been recently shown that [FeCl2(dppe)]n can be conveniently synthesised in high yield (ca. 80%) by treatment of FeCl2•4H2O with 1,2-bis(diphenylphosphino)ethane in acetone / chloroform mixtures [44,54] thereby avoiding the tedious preparation, or considerably greater cost, of anhydrous FeCl2 (As of March 2016 FeCl2•4H2O costs ~A$65 per mole and FeCl2 ~A$390 per mole, prices from Sigma Aldrich).…”
Section: Fecl(dppe)cp*mentioning
confidence: 99%